The Role of Prince Ronggosukowati in the History and Culture of Pamekasan - Noviyanti Supriliyanti; Ahmad Sudi Pratikno (PANTUN: Jurnal Ilmiah Seni Budaya, 2024)
Folklore serves as a bridge connecting generations and allows communities to maintain their cultural heritage amidst changing times. Folklore is a national cultural heritage that has values that can be taken and applied in the present and the future, as well as the spread of folklore by word of mouth. This study aims to describe the role and values contained in Prince Ronggosukowati, an important figure in the history and culture of Pamekasan. The research method used in this study is field research. Data collection techniques include literature studies, documentation, and interviews. The findings show that the role of Prince Ronggosukowati has a significant influence on the cultural and historical identity of Pamekasan, as well as contributing to the fields of culture, education, and religion. His life story is reflected in various Madurese literary and folklore works, making him a symbol of pride and community identity. The historical and cultural perspective on Prince Ronggosukowati shows the importance of the role of local leadership in shaping the cultural character of a region, which is in line with the view that folklore contains values that apply in society and need to be introduced to the younger generation. Prince Ronggosukowati’s influence is not only seen in infrastructure and government, but also in the preservation of cultural traditions that are the identity of the Pamekasan community.